2016
DOI: 10.1039/c5sc03045e
|View full text |Cite
|
Sign up to set email alerts
|

A NIR dye with high-performance n-type semiconducting properties

Abstract: A novel hetero-polycyclic aromatic compound showing strong NIR absorption and high-performance n-type semiconducting properties is developed. A special metal-free C–C coupling serves as a pivotal step in constructing the polycyclic π-framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 37 publications
(16 reference statements)
0
30
0
Order By: Relevance
“…Although calculations predict that the dimers should be significantly twisted (dihedral angle between 111° and 123°), OTFTs still exhibit promising performances (Table S2, Supporting Information). Furthermore, a chemically fused dimer, SM13, was reported by Pei and Zhao; calculations suggested that this dimer should be close to coplanar. This molecule exhibited a remarkably low LUMO level of −4.72 eV, measured by cyclic voltammetry, in combination with a low optical bandgap close to 1.1 eV.…”
Section: N‐type Organic Semiconductorsmentioning
confidence: 99%
“…Although calculations predict that the dimers should be significantly twisted (dihedral angle between 111° and 123°), OTFTs still exhibit promising performances (Table S2, Supporting Information). Furthermore, a chemically fused dimer, SM13, was reported by Pei and Zhao; calculations suggested that this dimer should be close to coplanar. This molecule exhibited a remarkably low LUMO level of −4.72 eV, measured by cyclic voltammetry, in combination with a low optical bandgap close to 1.1 eV.…”
Section: N‐type Organic Semiconductorsmentioning
confidence: 99%
“…They found that the maximum absorption energy decreased linearly versus the inverse square length of the conjugated system, and the absorption maxima of pentarylenediimide and hexarylenediimide were at 877 and 953 nm, respectively . Nevertheless, there has been limited number of successful examples of stable NIR absorption molecules through extending the π‐system utilizing polycyclic units because: 1) the conjugation saturation usually appears with band gap higher than 1.4 eV in many previously reported studies, attributing to the effective conjugated length (ECL) effect; 2) to narrow the band gap, the lowest unoccupied molecular orbital (LUMO) has to be lowered and/or the highest occupied molecular orbital (HOMO) energy level elevated; however, over‐elevating the HOMO would induce the instability of the compounds in air; and 3) the construction of elongated fused aromatics remains highly challenging owing to the tediousness of synthetic chemistry and poor solubility of the products.…”
Section: Methodsmentioning
confidence: 99%
“…Thec yclic voltammograms of both compounds showed four reversible reduction peaks with the first half-wave potentials at À0.87 V for 5 and À0.68 Vfor 6 vs.Fc/Fc + ,suggesting strong electronaccepting ability.T he LUMO levels were determined to be À4.10 eV for 5 and À4.27 eV for 6,from the onset potentials of the first reduction peaks,i mplying potential air-stable ntype semiconductors. [16] Theenergy gap E g estimated from the edge of the absorption spectra in CHCl 3 is 2.12 eV for 5 and 1.83 eV for 6.C alculations of nuclear independent chemical shifts (NICS) at the DFT-PBE0/6-31G(d) level indicate that the naphthalene subunits with imide groups show aromatic character whereas the naphthalene subunits with annulated benzene rings exhibit an antiaromatic feature and the annulated benzene rings exhibit aromaticity (Figure 4).…”
Section: Methodsmentioning
confidence: 99%